In silico analysis of carbohydrate-binding pockets in the lectin genes from various species of Canavalia. (June 2021) - Nivetha, Ramanathan; Meenakumari, Mani; Bhuvaragavan, Sreeramulu; Hilda, Karuppiah; Janarthanan, Sundaram
Graphical abstract: Highlights: Amplification and sequencing of lectin genes from three species of Canavalia . Experimental analysis of haemagglutination and carbohydrate specificities of seed extract. In silico analysis of deduced lectins' structures and their docking to carbohydrates. Carbohydrate specificities provide insights in potential antibiosis property of lectin. Abstract: Legumes are endowed with an opulent class of proteins called lectins that can detect tenuous variations in carbohydrate structures and bind them reversibly with high affinity and specificity. The genus Canavalia, in the family of Leguminosae, is considered to be an affluent source of lectin. An effort has been made to analyse the sequences encoded by the lectin gene and its carbohydrate binding pockets from three species of Canavalia, including C. virosa, C. rosea, and C. pubescens . Crude seed extract showed highest haemagglutination titer against buffalo RBCs and has high affinity to mannose and trehalose. Amplification of the lectin gene by gene-specific primers showed the presence of an 870 bp amplicon. Physicochemical characterization using various bioinformatic tools showed that the isoelectric point was below 7, suggesting that lectin molecules were acidic. A high aliphatic index and high instability index were observed, which indicated that lectin molecules were stable towards a wide range of temperatures. The occurrence of N-glycosylation sites at two sites was also identified in all three species. Prediction of secondary structure showed that approximately 59.05 %, 56.76 % and 54.88 % of the elements were random coils in the case of C. virosa, C. pubescens and C. rosea, respectively. Comparative modelling of the proteins and docking of hypothetical models with sugar moieties that inhibited the agglutination activity suggested that asparagine, serine, alanine, valine, tyrosine and threonine were the major residues involved in hydrogen bonding and other stacking interactions. This can further provide insights on its prospective antibiosis property.